Meta-análise do desempenho e características da carcaça e carne de cordeiros - Antônio, Simone De David (2017)
The objective of this study was to group information on the feeding systems used in the finishing of lambs, through a joint analysis. The data came from experiments conducted at Sheep Laboratory of the Universidade Federal de Santa Maria, from 1996 to 2017. In this period, 26 studies have been developed, 19 master dissertation and seven doctoral thesis. The feed systems to which the animals were submitted were: feedlot, pasture with supplementation, pasture without supplementation and high concentrate feedlot. The performance and carcass characteristics were evaluated in more than 590 lambs. Feeding system high concentrate presented the highest average daily gain (ADG) and better alimentary conversion. The feeding systems did not influence the percentage of the carcass cuts of the leg, shoulder and ribs. The feed system high concentrate feedlot presented higher values for carcass compactness and carcass subcutaneous fat thickness. The data of the fatty acids profile, fat content and cholesterol of the meat were also evaluated. Samples of the Longissimus muscle of 129 lambs were evaluated. The data were grouped according to the main feeding systems and considering forage types and concentrate proportion in diets: animals finished in feedlot and animals finished in pasture. Meat from lambs finished in pasture presented lowest fat level and cholesterol. The Lipid profile and fatty acids nutritional ratio were favorable in meat from animals finished in pasture. The methodology of determination of the carcass composition of lambs, mainly of the fractions of muscle, bone and fat and their relationships, was analyzed. Carcasses of 144 lambs were evaluated. Through the joint analysis it was possible to compare which cut represents the best composition of the carcass. Three groups or treatments were defined: half carcass dissection, shoulder dissection and leg dissection. The muscle fraction was larger in the leg, while the fat fraction showed a higher proportion in the shoulder cuts and in the half carcass. For the relationships between muscle and fat (M:F) and muscle and bone (M:B), the leg cut presented higher values compared to the shoulder and the half carcass, which were similar to each other. The analysis showed that the shoulder cut represents the tissue composition of the carcass. Feeding systems used in finishing lambs influence their performance, carcass characteristics and the quality of the meat produced.